Validation of vitiligo impact scale-22 among North Karnataka population - Anusha Shivaswamy; Aparna Palit; Arun C Inamadar (Wolters Kluwer Medknow Publications, 2020)
Background: Vitiligo is known to have major psychosocial impact among the sufferers. "Vitiligo impact scale-22 (VIS-22)" is a recently developed specific scale to measure quality of life (QOL) in these patients. It was found effective in evaluating QOL among north Indian patients with vitiligo. Since the effect of vitiligo on QOL is variable, it is prudent to validate VIS-22 in various populations. Aim: This study aims to validate VIS-22 among south Indian patients with vitiligo. Methods: Vitiligo patients with education up to 10th standard were included as cases. Patients suffering from short-term illnesses served as controls. Cases and controls were given visual analog scale (VAS), dermatology life quality index (DLQI), Skindex-16 and VIS-22 to respond at 1st, 2nd, and 12th weeks. The criterion and construct validities of the scales were evaluated using Spearman's correlation coefficient (r). Student's t-test was used for disease specificity of VIS-22. Spearman's rank coefficient, paired t-test, and ANOVA were used to estimate first, second, and third measures of responsiveness, respectively. Results: A total of 153 cases and 155 controls were enrolled. The criterion validity showed strongest correlation with Skindex-16 (r = 0.832) and convergent validity with both DLQI (r = 0.752) and Skindex-16 (r = 0.832). It also showed strong correlation with emotional and functioning domain of Skindex-16 at baseline (r = 0.713 and 0.702, respectively) and at 12 weeks (r = 0.770 and 0.789, respectively). The scales were reliable at baseline and 2 weeks with excellent correlation between scores (r = 0.954). The VIS-22 scores were responsive at week 12 and similarly in VAS, DLQI, and Skindex-16. Conclusion: VIS-22 has vitiligo-specific questions and better QOL measurement properties compared to DLQI and Skindex-16. This study results found VIS-22 to be a valid, highly reliable, and responsive QOL-measurement tool among south Indian patients with vitiligo.